(untitled) (Revista de Medicina Clinica, 2018)
Introduccion: Cerebral vasospasm is a severe complication that occurs in up to 70% of patients with aneurysmal subarachnoid hemorrhage. Its presence is initiated by the presence of blood in the subarachnoid space and the presence of inflammatory response in the central nervous system. Clinically, it manifests as a delayed neurological deficit due to delayed cerebral ischemia, or focal symptoms due to cerebral infarction secondary to occlusion of cerebral arteries. The diagnosis can be non-invasive with angio-tomography, angio-resonance or transcranial Doppler, or invasive with substraction digital angiography. It is classified as symptomatic or asymptomatic. Its treatment implies maintaining adequate cerebral perfusion pressure through general and specific medical treatment, and in cases where the symptoms do not respond to treatment, the use of chemical or mechanical angioplasty. Rev Med Clin 2018; 2 (1): 8-12.